A Qualitative Synthesis of the Effects of Rising Cost-Sharing Requirements in the United States - Goldstein, Evan Victor (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2019)
In this review, I evaluate and synthesize thematic findings from the past decade of qualitative research on the effects of high and increasing cost-sharing requirements on health care utilization from patient and provider perspectives. Whereas most of the literature on cost-sharing and health services utilization behavior has been quantitative in approach, this synthesis helps us examine patient and provider perceptions and the lived experiences associated with high and increasing health insurance cost-sharing requirements. First, I find that high and increasing cost-sharing requirements lead American patients to forgo a range of health care services, even medically-necessary treatment for themselves and their family members, and even among employed and middle-class American families who have insurance coverage. Second, I demonstrate that high cost-sharing expenses beget intense patient confusion, fear, stress, and anxiety. These findings complement results from the RAND Health Insurance Experiment, a large experimental study of health care costs and utilization conducted from 1971 to 1986, to improve our understanding of the effects of high cost-sharing requirements on patient health care utilization in the modern context. This is critical because some policymakers continue to espouse higher patient cost-sharing requirements. Limitations and future directions for research are discussed.